2005
DOI: 10.1007/s11897-005-0013-3
|View full text |Cite
|
Sign up to set email alerts
|

Imaging the renin-angiotensin-aldosterone system in the heart

Abstract: The influence of the renin-angiotensin system (RAS) is recognized in cardiac and vascular injury. An extrinsic RAS has been known for decades, and an equally important intrinsic RAS has been discovered recently. The latter leads to pathologic tissue alterations in the absence of systemic stimuli and may be the main source of local tissue effects of RAS. A new radiotracer fluorobenzoyl-lisinopril was synthesized by radiolabeling benzoic acid active ester with 18F and reacting that with the epsilon-amino group o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Also, Schuster's group has reported that both the cis and the trans isomer of FCAP exist in plasma, inferring that isomeric conversion is a phenomenon that occurs in vivo (34). Finally, captopril is thought to have a higher affinity for plasma ACE than the tissue ACE, whereas other ACE inhibitors, such as lisinopril, have a higher affinity for tissue ACE than vascular ACE (12)(13)(14)35). Because our goal is to study ACE in heart tissue, the compounds with higher tissue affinity would be more suitable starting motifs for the design of novel radioligands.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, Schuster's group has reported that both the cis and the trans isomer of FCAP exist in plasma, inferring that isomeric conversion is a phenomenon that occurs in vivo (34). Finally, captopril is thought to have a higher affinity for plasma ACE than the tissue ACE, whereas other ACE inhibitors, such as lisinopril, have a higher affinity for tissue ACE than vascular ACE (12)(13)(14)35). Because our goal is to study ACE in heart tissue, the compounds with higher tissue affinity would be more suitable starting motifs for the design of novel radioligands.…”
Section: Discussionmentioning
confidence: 99%
“…We used 99m Tc because of its excellent imaging characteristics and widespread availability (9), as well as the suitability of the previously described technetium-tricarbonyl (Tc(CO) 3 ) core (10) to form robust complexes with our recently described single amino acid chelate technology based on the di(pyridylmethyl)amine chelator (11). We chose lisinopril as the starting structural ACE inhibitor motif because of its higher affinity for tissue ACE (12)(13)(14) and the chemical flexibility it offers to incorporate di(pyridylmethyl)amine moiety. This article describes the first, to our knowledge, high-affinity, low molecular weight, 99m Tc-labeled compound that shows specific binding to ACE in vivo.…”
mentioning
confidence: 99%
“…It was used in ACE imaging from three different approaches: I-125 labeled benzamidine analog 125 I-351A 72 and technetium-99m labeled compound 99m Tc-lisinopril 73 , 74 for SPECT imaging, as well as the F-18 labeled benzoyl analog 18 F-fluorobenzoyl lisinopril 75 for PET imaging (Figure 5 ). While maintaining the inhibition of ACE, they all successfully visualized the distribution of ACE while blocking studies proved specificity in vivo 76 , 77 . An 11 C tracer derived from ACE inhibitor zofenopril (Figure 5 ) was reported by Matarrese et al and evaluated first-hand in human.…”
Section: Renin-angiotensin Aldosterone System Imagingmentioning
confidence: 99%
“…Although extrinsic systemic RAS mediators regulate physiological processes throughout the body, there is also an intrinsic cardiac RAS that is activated by myocardial injury and exerts harmful local effects including development of myocyte hypertrophy, interstitial and perivascular collagen deposition, and myocyte apoptosis. 131,132 As in the systemic circulation, myocardial angiotensin I is modified by ACE to angiotensin II (at concentrations more than 100 times that in the plasma), which binds to myocardial angiotensin II receptors-AT 1 R and AT 2 R-with stimulation of the former (eg, in the postinfarction state) shown in animal studies to cause fibrosis and ventricular remodeling and increase mortality. [133][134][135][136] As pharmacologic blockage of this system by ACE-I-and ARB (AT 1 R)-binding agents ameliorate many deleterious processes in HF, radiotracer-labeled ACE-I and ARBs provide a way to visualize activity of the myocardial RAS.…”
Section: Imaging Remodeling Processesmentioning
confidence: 99%
“…Among the first such tracers investigated was 18 F-fluorobenzoyl lisinopril (FBL), which binds to ACE. 132,137 Dilsizian et al incubated fluorobenzoyl lisinopril in vitro with explanted hearts from 3 patients with ischemic cardiomyopathy who had undergone cardiac transplant and found that tracer binding was nonuniform-highest in periinfarcted tissue (detected by picrosirius red staining of collagen replacement fibrosis), followed by infarct tissue, with the lowest uptake in the remote noninfarcted myocardial segments. These findings suggest a potential radionuclide imaging method of monitoring disease progression and assessing effectiveness of standard ACE-I therapy in patients with HF.…”
Section: Imaging Remodeling Processesmentioning
confidence: 99%